ISSUES AND VIEWPOINTS OF SCIENTIFIC RESEARCH IN THE FIELD OF DESIGNING ENERGY EFFICIENT BUILDINGS IN UZBEKISTAN - ELENA SCHIPACHEVA; RAKHMATULLO PIRMATOV; KHABIBULLO PIRMATOV; JASUR RASHIDOV (International Journal of Multidisciplinary Research and Studies, 2022)
This research paper provides the main issues that need to be addressed for the development of a domestic scientific school on the design of energy-efficient buildings and discusses issues pertaining to their widespread introduction in the Republic of Uzbekistan. In addition, this paper presents the results of the scientific research carried in this field at the Tashkent State Transport University.